Career Preferences and Factors Influencing the Career Choice of Senior High Students of a Catholic School - Julde E. Dangoy; Dennis V. Madrigal (Philippine Social Science Journal, 2020)
The adolescent stage is considered one of the challenging stages in human development. A stage where a student is planning and preparing himself in a role, he would like to take part in the community by taking his desired course or job to uplift his dignity as a person. Career decision making is undoubtedly one of the most difficult and challenging in any students' life. As students continue to college, wisely choosing a career greatly impacts their future career life. For some instances, changing courses could be a cause of having the wrong decision in choosing a career that could lead to a waste of time, resources, and career frustration. Hence, the paper assessed the degree of career preferences and the extent of factors influencing the career choices of senior high school students in a Catholic School in Antique during the school year 2019-2020. Likewise, it compared the students 'career preferences and factors influencing career choices in terms of their demographics. Also, it correlated career preferences and the influence of factors in career choices.